Graphic narrative and its semantic value in the designs of the incident of the Taff: رغد فتاح راضي (Al-Academy, 2021)
The concept of narration stems from the connotation of continuous communication through which narration is manifested as a message that is exchanged between the sender and the recipient, and that narration is an educational conceptual necessity, representing the philosophy of intellectual inclusion achieved in a direct speech to the mind, but it is encapsulated in a colorful frame that attracts the soul and attracts attention, and the graphic narration is a speech A visual based on the basis of interference and sequence of the event in weaving the elements in a consensual way through a continuous communication process that begins with the embodiment of an event - an important event - to the recipient, in which an intellectual employment of all energies and values is expressed in the recipient, and the effect and visual tension of the recipient is achieved and the interaction is reflected in terms of position and biography.The graphic narration is a visual discourse based on weaving successive events within the interrelated relationships of the components of the design structure, its construction depends on the knowledge and cultural experiences of the event designer and the degree of its influence and the rumors of a feeling reflected in building the formal configuration of the design, and the expression of intellectual contents in a visual language that may be direct (realistic simulation) ), Or indirectly (semantic symbols) or both together, up to the content of the design idea and achieving its functional and aesthetic goals